Re–Os Geochronology on Molybdenites from the Donggebi Mo Deposit in the Eastern Tianshan of the Central Asia Orogenic Belt and its Geological Significance. Issue 2 (April 2014) - Han, Chunming; Xiao, Wenjiao; Zhao, Guochun; Sun, Min; Qu, Wenjun; Du, Andao
Abstract: The Donggebi Mo deposit is located in the eastern section of the Eastern Tianshan Orogenic Belt, Central Asia Orogenic Belt. Rhenium and osmium isotopes of molybdenites from the Donggebi porphyry Mo deposit have been used to determine the timing of mineralization and the source of osmium and, by inference, ore metals. Molybdenite was collected mainly from a granite porphyry stock, which is characterized by moderate to strong silicification. Rhenium concentrations in molybdenite samples are between 10 and 63 μg g −1 . Analysis of eight molybdenite samples yields an isochron age of 234.3 ± 1.6 Ma (2σ) with an initial 187 Os of 0.04 ± 0.45 (MSWD = 0.25). The data support the hypothesis that a significant part of the metals and magmas have a mixed (crust + mantle) origin. Based on the geological history and spatial‐temporal distribution of the granitoids, it is proposed that the Mo deposits in the eastern part of the East Tianshan Orogenic Belt were related to a post‐collision extensional setting in the Early Mesozoic. Abstract : The Donggebi Mo deposit is located in the Eastern Tianshan 0rogenic Belt, Central Asia Orogenic Belt→Analysis of eight molybdenite samples yields an isochron age of 234.3 ± 1.6 Ma →Mo deposits in the eastern part of the East Tianshan Orogenic Belt occurred in the Early Mesozoic.